Akibat Hukum Akta Autentik yang Dibacakan Oleh Pegawai Notaris Kepada Para Pihak - Nyarong, Theodhorus Thrieyadi; Pramana, I Gede Pasek (Acta Comitas; Vol 6 No 02 (2021)DO - 10.24843/AC.2021.v06.i02.p07, 2021)
Abstract The purpose of this scientific article is to find out the arrangements related to the reading of authentic notary deeds and to analyze the juridical consequences of authentic deeds read by notary employees to the parties. This article is classified as a type of normative research that uses 2 types of approaches, namely the statutory and conceptual approaches. The arrangement regarding the reading of the Notary's Authentic Deed is contained in Article 16 paragraph (1) and letter m on article 16 which means that a Notary is obliged to read the Deed made in front of the parties - the parties in this case the parties making the Deed who are attended by witnesses. It’s very important that the deed is read in front of the parties - the party facing the parties and is an obligation based on the philosophical elements contained in the process of reading the deed. The juridical consequence of the authentic deed read out by the notary employee to the parties is the reading of the deed which is not carried out by the Notary but is carried out by the staff of the Notary to the parties as regulated in Article 16 paragraph (9) UUJN which in principle has the consequence that the authentic deed will be degraded into a deed. under the hand, which before the deed has perfect proof is no longer perfect. However, this legal consequence is exempted from the will deed as referred to in Article 16 paragraph (10) UUJN. Abstrak Tujuan daripada artikel ilmiah ini yaitu untuk mengetahui pengaturan terkait pembacaan akta autentik Notaris dan menganalisis konsekuensi yuridis dari akta autentik yang dibacakan oleh pegawai notaris kepada para pihak. Artikel ini tergolong jenis penelitian normatif yang menggunakan 2 jenis pendekatan yaitu pendekatan perundang-undangan dan konseptual. Pengaturan Terkait Pembacaan Akta Autentik Notaris termuat dalam Pasal 16 ayat (1) dan huruf m pasal 16 UUJN yang bermakna yaitu seorang Notaris diwajibkan untuk membacakan Akta yang dibuat dihadapan pihak – pihak penghadap yang dalam hal ini para pihak yang membuat Akta tersebut yang dihadiri saksi-saksi. Menjadi teramat penting akta dibacakan dihadapan pihak – p i hak penghadap dan merupakan suatu kewajiban yang didasarkan kepada unsur filosofis yang terdapat pada proses pembacaan akta tersebut. Konsekuensi yuridis dari  atas akta autentik yang dibacakan oleh pegawai notaris kepada para pihak yaitu pembacaan akta yang tidak dilakukan oleh Notaris namun dilakukan oleh pegawainya Notaris kepada para pihak sebagaimana diatur pada Pasal 16 ayat (9) UUJN yang pada prinsipnya memiliki konsekuensi bahwa akta autentik tersebut akan terdegradasi menjadi akta dibawah tangan, yang sebelum akta tersebut memiliki pembuktian yang sempurna menjadi tidak sempurna lagi. Namun akibat hukum ini dikecualikan untuk akta wasiat sebagaimana Pasal 16 ayat (10) UUJN.